The response of Petunia × atkinsiana 'Pegasus Special Burgundy Bicolor’ to mechanical stress encompassing morphological changes as well as physiological and molecular factors - Natalia Kuźma; Magdalena Klimek-Chodacka; Robert Budzyński; Rafał Barański; Agata Jędrzejuk (Scientific Reports)
Abstract In 1973, Jaffe identified and characterized the phenomenon of thigmomorphogenesis, also referred to as mechanical stress (MS) or mechanical stimulation in plants. Previous studies on petunia plants demonstrated that MS significantly affects growth dynamics. As a response to MS, petunias exhibit increased levels of indole-3-acetic acid (IAA) oxidase and peroxidase, although the active transport of endogenous IAA remains unaffected. Furthermore, earlier research has shown that MS inhibits the synthesis of IAA and gibberellin (GA3), with noticeable effects on the 14th day of mechanical stimulation. The current experiment made on Petunia × atkinsiana 'Pegasus Special Burgundy Bicolor’ focused on evaluating the morphological and physiological responses to MS, along with the expression of specific touch-responsive genes such as GH3.1, which is involved in auxin metabolism, and calmodulins (CaMs), playing an important role in stress responses. GH3.1 expression was found to be negatively correlated with IAA synthesis while positively correlated with GAs synthesis and IAA oxidase activity. Variable expression patterns were observed in the calmodulins: CAM53 and CAM81 expression positively correlated with IAA synthesis and plant height, whereas CAM72 expression was positively associated with GAs levels and IAA oxidase activity in plants touched 80× per day, but all of them were negatively related to IAA content and shoot increment, while positively related to GAs synthesis and IAA oxidase activity.